NILAI-NILAI PENDIDIKAN KARAKTER YANG TERKANDUNG DALAM MONUMEN PERANG KEMERDEKAAN BENTENG HURABA DI KECAMATAN BATANG ANGKOLA KABUPATEN TAPANULI SELATAN TAHUN 2020 - Parmohonan Lubis (Jurnal Education and Development, 2021)
This research aims to find out how far is educational caracter value in independence war monument in Benteng Huraba Batang Angkola sub district. The type of this research was a qualitative research by using research historical methods. There were four stages of historical research methods, they were: The first was a heuristic that was finding and collecting both oral and written sources. Historical sources obtained by interview and documentation. Second was the criticism / verify the authenticity and validity analyzes the sources were obtained. The third interpretation of the techniques of data interpretation. Fourth was the historiography of the writing or presentation of the data by using the rules of scientific writing. This research is done by using observation, interview and documentation, they ar to see educational caracter value in independence war monement in Benteng Huraba sub district. The informan of this research is the people who insolve inthis research. They are: society who live around independence war monument in Benteng Huraba sub district consist of society leader and the society themselves. The instument of this research is the interview which is made directly. Educational caracter value in independence war monument in Benteng Huraba sub district is the history estate in Benteng Huraba which is the evidence of society struggle in maintainingthefending their area. This struggle gives contribution to the society around in getting the education. By this history, the spirit of togetherness and nationalism spirit will grow in the society.